Sertifikasi Halal Daging Sapi Potong Sebagai Upaya Perlindungan Konsumen Muslim di Pasar Rawa Indah Kota Bontang - Azzahratul Azkiya; Siti Azizah (LPPM IAI Nasional Laa Roiba Bogor, 2023)
Indonesia is a country with the biggest amount of Muslim population in terms of adhering to the religion of Islam The issue of halal food is a sensitive issue in society. The government has a huge responsibility to protect the entire society, especially the consumer, ensuring the halal status of the distributed products in the market. The purpose of this research is to learn about the mechanism of halal certification for beef that is done in Technical Implementation Unit of Slaughterhouse in Bontang to be distributed in Rawa Indah Market of Bontang and to learn about halal certification implementation as a fulfillment of consumer rights and obligation of business actor in an effort to protects Muslim consumers in Rawa Indah Market of Bontang. The result of the research is expected to be used as a source of information for Muslim consumers about the halal certification implementation of beef and as an evaluation for business actors to perform their obligation of providing consumer protection. The data is obtained from interviews using unstructured interview method with several informants directly (face to face) and indirectly (WhatsApp). In addition, data collection is done by doing a survey that is filled by 30 participants who are Muslim consumers in Rawa Indah Market of Bontang, survey is done using Google Form. The research methodology used in the study is descriptive qualitative approach. The result of the research is that Technical Implementation Unit of Slaughterhouse in Bontang has done halal certification in accordance with the regulation although there are difficulties in the process of halal certification. The business actors in Rawa Indah Market of Bontang also understand halal certification and implement it by sending cows to be butchered in Technical Implementation Unit of Slaughterhouse in Bontang that is already certified as halal. Muslim consumers in Rawa Indah Market understand halal certification but are not able to determine a product’s halal status without the halal label and halal certificate. Beef sold in the traditional market or modern market comes from halal certified slaughterhouses. The process of butchering follows a standard ASUH concept (Aman, Sehat, Utuh, Halal) in accordance with the Islamic Sharia. Consumer protection is not only the obligation of business actors but also the government entity such as providing socialization about halal certification and consumer protection. The implementation of halal certification and halal label is a fulfillment of Muslim consumers right to get the product they desire.